Bifurcation analysis for a singular differential system with two parameters via to topological degree theory - Liu, Lishan; Sun, Fenglong; Zhang, Xinguang; Wu, Yonghong (Nonlinear Analysis: Modelling and Control, 2017)
Based on the relation between Leray–Schauder degree and a pair of strict lower and upper solutions, we focus on the bifurcation analysis for a singular differential system with two parameters, explicit bifurcation points for relative parameters are obtained by using the property of solution for the akin systems and topological degree theory.
Keywords: Leray–Schauder degree; bifurcation analysis; singular differential system; two parameters; strict lower and upper solutions